The effect of competition on gamma-glutamyl transferase, creatinine and protein levels of taekwondo players - (:unkn) unknown (ACADEMIC JOURNALS, 2012)
Post-exercise proteinuria and increased urinary gamma-glutamyl transferase (GGT) levels can be predictive of exercise induced renal damage. In the literature, numerous studies exist on exercise induced proteinuria, but studies investigating the effects of exercise on urinary GGT levels are quite few in martial arts. The purpose of this study was to determine that changes in serum and urinary GGT activity and creatinine levels, and also urinary protein levels in order to assess any potential exercise induced tubular damage on taekwondo players. The study was performed on 18 female and 17 male taekwondo players who were participants in Istanbul Taekwondo Championships. Blood and urine samples collected pre- and 1 h post competition were analyzed for serum GGT and creatinine, urinary GGT, creatinine and protein levels. The post competition serum creatinine level (p = 0.002), urinary GGT (p = 0.010) and protein levels (p = 0.000) were higher than the pre- competition levels in female players. The post competition serum creatinine level (p = 0.006), urinary GGT (p = 0.005) and protein levels (p = 0.000) were higher than the pre-competition levels in male players. We suggest that high-intensity short duration exercise does not lead to increase in serum GGT levels, but lead to increase in serum creatinine levels, as well as induced excretion urinary GGT and protein levels.
Keywords: Exercise; gamma-glutamyltransferase; serum; urine; enzyme; protein; creatinine; taekwondo; BODY-MASS INDEX; RENAL-FUNCTION; EXERCISE; MARATHON; LIVER